Research on PVT Solution Methods for Navigation Message of GPS Receiver - Zhou Fan (Institute of Advanced Engineering and Science, 2014)
On the basis of the analysis of PVT solution methods for navigation message, the solution procedure of evaluation algorithm of LSM and Kaman filtering evaluation algorithm is constructed. Further, based on OEM development board for data acquisition, PVT solution process of collected GPS signals is simulated, and the results show that the solution property of Kaman filtering algorithm is much better than LSM. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4177